Manajemen Sarana dan Prasarana Dalam Pengelolaan Sekolah Sehat di SD Negeri Tempel Surakarta - Saputri, Ayunda Nadea; Nisa, Choirun (Journal of Smart Education and Learning, 2025)
A clean and healthy school environment involves not only physical cleanliness but also balanced nutrition, physical activity, and attention to students’ mental and emotional well-being. This study aims to examine the management of facilities and infrastructure in implementing a healthy school program at SD Negeri Tempel Surakarta. A qualitative case study approach was employed, using observation, interviews, and documentation as data collection techniques. Non-participatory observation was applied, in which the researcher observed activities without direct involvement, complemented by interviews and documentation of healthy school practices. The findings indicate that the school has demonstrated effective and creative management of facilities and infrastructure to support the realization of a healthy school environment. Strong commitment from the principal and teachers further reinforces this effort. However, challenges remain, as some students still tend to dispose of waste improperly and rarely wash their hands. These issues may be addressed through consistent guidance, regular practice, and sustained motivation to encourage healthier habits.